Geospatial analysis with landsat series and sentinel-3B OLCI satellites to assess changes in land use and water quality over time in Brazil (2022)
Geospatial analyses have gained fundamental importance on a global scale following emphasis on sustainability. Here we geospatially analyze images from Landsat 2/5/7/8 satellites captured during 1975 to 2020 in order to determine changes in land use. Sentinel-3B OLCI (Ocean Land Color Instrument) images obtained in 2019 and 2021 were utilized to assess water resources, based on water turbidity levels (TSM_NN), suspended pollution potential (ADG_443_NN) and the presence of chlorophyll-a (CHL_NN) in order to temporally monitor the effectiveness of Brazilian legislation currently in force. This work on sustainability standards was applied to a hydrographic basin dedicated to agricultural production located in southern Brazil. Satellite images from Landsat 2/5/7/8 (1975 to 2020) and Sentinel-3B OLCI (2019 and 2021) revealed that changes in land use, vegetation cover and water in the Capinguí Dam reservoir detected high concentrations of ADG_443_NN (3830 m−1), CHL_NN (20,290 mg m−3) and TSM_NN (100 gm−3). These results can alert the population to the risks to public health and harm to hydrographic preservation, capable of covering large regions.